2018
DOI: 10.1016/j.ijnurstu.2018.08.013
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the experiences of vulnerable people participating in research on sensitive topics

Abstract: Although researchers frequently experience obstacles and the phenomenon known as "gatekeeping" when attempting to conduct research amongst vulnerable populations, there is little evidence of harm to participants. On the contrary, there is evidence of benefit for participants and evidence that they are willing to participate if given the opportunity. Although well-meaning, the actions of gatekeepers are not only paternalistic, they could be further marginalising vulnerable populations by denying them the benefi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
65
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 43 publications
3
65
0
Order By: Relevance
“…In addition to the concerns about privacy, participants expressed a desire for reassurance that they could trust the research team, and to that end, it was important that study procedures were clearly explained so that they could weigh the risks of participating with potential benefits. This speaks to the importance of autonomy in decision-making and informed consent practices, whereby participants’ ability to weigh the costs and (potential) benefits of participation and to make the decision for themselves should be valued and respected (Alexander et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the concerns about privacy, participants expressed a desire for reassurance that they could trust the research team, and to that end, it was important that study procedures were clearly explained so that they could weigh the risks of participating with potential benefits. This speaks to the importance of autonomy in decision-making and informed consent practices, whereby participants’ ability to weigh the costs and (potential) benefits of participation and to make the decision for themselves should be valued and respected (Alexander et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite bioethical, legal, and social concerns regarding the risks and benefits of research participation for pregnant and postpartum women who use alcohol and drugs (Davis, et al 2019 ), the inclusion of vulnerable populations who are marginalized or stigmatized in research on sensitive topics has not demonstrated undue harm or exposure to unacceptable risk, and in fact, has been associated with potential benefits, such as altruism, catharsis, and gained knowledge (Alexander, Pillay, & Smith, 2018 ). Of course, it is important for researchers to adopt careful experimental design and safeguards that will uphold the principal of non-maleficence and protect vulnerable participants from harm (Alexander et al, 2018 ; Sikeweyiya & Jewkes, 2013 ). Exclusion of substance using populations may violate important bioethical principles of human subjects research, particularly the principles of autonomy, beneficence, and justice (Alexander et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Horowitz and colleagues [17] have even argued that participants in any research are vulnerable to some degree. All of this attains particular relevance in sensitive research, since asking people about their experiences connected with sensitive topics is considered to render the participants vulnerable [18].…”
Section: Invisible Vulnerabilitiesmentioning
confidence: 99%
“…Other studies have also shown that vulnerable subjects are willing to discuss sensitive topics, often welcoming the opportunity to talk about their experience. Participants in those studies stated that they experienced some positive outcomes of their participation, including a therapeutic benefit, catharsis, new knowledge, altruism, empowerment and a new perspective on or understanding of the event or experience about which they were being interviewed [18,19].…”
Section: On the Productive Potential Of Researching Vulnerable Subjectsmentioning
confidence: 99%